Kinsenoside Alleviates Alcoholic Liver Injury by Reducing Oxidative Stress, Inhibiting Endoplasmic Reticulum Stress, and Regulating AMPK-Dependent Autophagy - Gao, Limin; Chen, Xingyu; Fu, Zeyu; Yin, Jie; Wang, Yafen; Sun, Weiguang; Ren, Hong; Zhang, Yonghui (Frontiers in Pharmacology, 2022)
Background: Anoectochilus roxburghii (Orchidaceae) is a traditional Chinese medicinal herb with anti-inflammatory, antilipemic, liver protective, immunomodulatory, and other pharmacological activities. Kinsenoside (KD), which shows protective effects against a variety types of liver damage, is an active ingredient extracted from A. roxburghii. However, the liver protective effects and potential mechanisms of KD in alcoholic liver disease (ALD) remain unclear. This study aimed to investigate the liver protective activity and potential mechanisms of KD in ALD. Methods: AML12 normal mouse hepatocyte cells were used to detect the protective effect of KD against ethanol-induced cell damage. An alcoholic liver injury model was induced by feeding male C57BL/6J mice with an ethanol-containing liquid diet, in combination with intraperitoneal administration of 5% carbon tetrachloride (CCl4) in olive oil. Mice were divided into control, model, silymarin (positive control), and two KD groups, treated with different doses. After treatment, hematoxylin–eosin and Masson's trichrome staining of liver tissues was performed, and serum alanine aminotransferase (ALT) and aspartate transaminase (AST) levels were determined to assess the protective effect of KD against alcoholic liver injury. Moreover, proteomics techniques were used to explore the potential mechanism of KD action, and ELISA assay, immunohistochemistry, TUNEL assay, and western blotting were used to verify the mechanism. Results: The results showed that KD concentration-dependently reduced ethanol-induced lipid accumulation in AML12 cells. In ALD mice model, the histological examination of liver tissues, combined with the determination of ALT and AST serum levels, demonstrated a protective effect of KD in the alcoholic liver injury mice. In addition, KD treatment markedly enhanced the antioxidant capacity and reduced the endoplasmic reticulum (ER) stress, inflammation, and apoptosis compared with those in the model group. Furthermore, KD increased the phosphorylation level of AMP-activated protein kinase (AMPK), inhibited the mechanistic target of rapamycin, promoted the phosphorylation of ULK1 (Ser555), increased the level of the autophagy marker LC3A/B, and restored ethanol-suppressed autophagic flux, thus activating AMPK-dependent autophagy. Conclusion: This study indicates that KD alleviates alcoholic liver injury by reducing oxidative stress and ER stress, while activating AMPK-dependent autophagy. All results suggested that KD may be a potential therapeutic agent for ALD.